INCIDENCE OF LOWER-EXTREMITY FRACTURES IN U.S. NURSING HOMES. (16th November 2018) - Sine, K; Lee, Y; Zullo, A; Daiello, L; Zhang, T; Berry, S
Abstract: Limited studies suggest lower extremity (LE) fractures are morbid events for nursing home (NH) residents. Our objective was to conduct a nationwide study comparing the incidence and potential risk factors associated with hip versus non-hip LE (femoral shaft and tibia-fibula) fractures in the NH. We included all U.S. long-stay residents aged ≥65 years enrolled in Medicare 1/1/2008–12/31/2009 (N=1, 257, 279). Residents were followed from long-stay qualification until the first event of LE fracture, death, or end of follow-up (2-years). Fractures were classified using Medicare diagnostic and procedural codes. Function, cognition, and medical status were obtained from the Minimum Data Set prior to long-stay qualification. Incidence rates (IR) were calculated as the total number of fractures divided by person-years. During 42, 800 person-years follow-up, 52, 177 residents had a LE fracture (43, 695 hip, 6, 001 femoral shaft, 2, 481 tibia-fibula). The unadjusted IR of LE fractures were 1.32/1, 000 person-years (95% CI, 1.27–1.38) for tibia-fibula, 3.20/1, 000 person-years (95% CI, 3.12–3.29) for femoral shaft, and 23.32/1, 000 person years (95% CI, 23.11–23.54) for hip. As compared with hip fracture residents, non-hip LE fracture residents were more likely to be immobile (58.1% vs 18.4%), dependent in all ADLs (31.6% vs 10.8%), transferred mechanically (20.5% vs 4.4%), overweight (mean BMI 26.6 kg/m2 vs. 24.0), and have diabetes (34.8% vs 25.7%). Our findings that non-hip LE fractures often occur in severely functionally impaired residents suggests these fractures may occur during lifting and transferring. The resident differences in our study highlight the need for distinct prevention strategies for hip and non-hip LE fractures.